The Economic Analysis of Fish Farming Business due to the Intervention of Community Direct Aid in Muaro Jambi Regency, Jambi Province, Indonesia - Darlim Darmawi; Jafrinur Jafrinur; Novirman Jamarun; Dwi Yuzaria; Roni Pazla (Universitas Andalas, 2019)
This study analyzes the existing fish farming economic aspects' due to Community Direct Aid (CDA) intervention in the fish production center in Muaro Jambi Regency, Jambi Province. The research methodology uses survey methods. The data collection tool uses a questionnaire survey, and data analysis uses descriptive analysis, mathematical analysis, and income analysis. As a result, the fish farming of catfish farmers can generate income in a total of Rp. 660,272.410,- with the ability to generate income in 511% and efficient in using production costs. The implications of government political policy intervention on farmers as the activator subject of the economic aspects of fish farming business raise six items (60%) have positive effects, and four items (40%) have adverse effects. In conclusion, the income of fish farming in conditions that can generate overall income. The impact of government policy intervention on farmers as the driving subject of aquaculture's economic aspects.